Identified novel heterozygous HTRA1 pathogenic variants in Chinese patients with HTRA1-associated dominant cerebral small vessel disease - Chen, Mei-Jiao; Zhang, Yi; Luo, Wen-Jiao; Dong, Hai-Lin; Wei, Qiao; Zhang, Juan; Ruan, Qi-Qi; Ni, Wang; Li, Hong-Fu (Frontiers in Genetics, 2022)
Background: Homozygous and compound heterozygous mutations in HTRA1 cause cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL). Recently, heterozygous pathogenic variants in HTRA1 were described in patients with autosomal dominant cerebral small vessel disease (CSVD). Here, we investigated the genetic variants in a cohort of Chinese patients with CSVD. Methods: A total of 95 Chinese index patients with typical characteristics of CSVD were collected. Whole exome sequencing was performed in the probands, followed by Sanger sequencing. Pathogenicity prediction software was applied to evaluate the pathogenicity of the identified variants. Results: We detected five heterozygous HTRA1 pathogenic variants in five index patients. These pathogenic variants included four known variants (c.543delT, c.854C>T, c.889G>A, c.824C>T) and one novel variant (c.472+1G>A). Among them, c.854C>T, c.824C>T, and c.472+1G>A have never been reported in China and c.889G>A was once reported in homozygous but never in heterozygous. Three of them were distributed in exon 4, one in exon 2, and another splicing variant in intron 1. Four out of five probands presented typical features of CARASIL but less severe. The common clinical features included lacunar infarction, cognitive decline, alopecia and spondylosis. All of them showed leukoencephalopathy and the main involved cerebral area include periventricular and frontal area, centrum semiovale, thalamus, and corpus callosum. Anterior temporal lobes and external capsule involvement were also observed. Three probands had intracranial microbleeds. Conclusion: Our study expanded the mutation spectrum of HTRA1 especially in Chinese populations and provided further evidence for “hot regions” in exon 1-4 especially in exon 4 in heterozygous HTRA1 pathogenic variants. Our work further supported that patients with heterozygous HTRA1 pathogenic variants presented with similar but less severe features than CARASIL but in autosomal dominantly inherited pattern.